Intracranial Compartment Volumes in Normal Pressure Hydrocephalus: Volumetric Assessment versus Outcome - Palm, W.M. (AJNR Am J Neuroradiol, 2006)
BACKGROUND AND PURPOSE: Although enlargement of the cerebral ventricles plays a central role in the diagnosis of normal pressure hydrocephalus (NPH), there are no reports on the use of volumetric assessment to distinguish between patients who respond to ventriculoperitoneal shunt surgery and those who do not. The purpose of this study is to explore the association between preoperative intracranial compartment volumes and postoperative improvement. METHODS: Twenty-six patients (17 men; mean age, 75 years [range, 54–87 years]) with a clinical or radiologic suspicion of NPH were included in the study. Gait, cognition, and bladder function were evaluated by clinical rating. MR imaging of the brain was acquired at 0.5T and 1.5T. Total intracranial volume, ventricular volume, brain volume, and pericerebral CSF volume were determined by volumetric assessment. Four imaging variables were determined: ventricular volume ratio, brain volume ratio, pericerebral CSF volume ratio, and the ratio of ventricular volume to pericerebral CSF volume. All patients underwent ventriculoperitoneal shunt surgery. RESULTS: Clinical follow-up was assessed 1 year after shunt surgery. No difference in the mean ventricular volume ratio, the mean brain volume ratio, the mean pericerebral CSF volume ratio, and the mean ratio between ventricular and pericerebral CSF volume was found between subjects who improved on gait or cognition or bladder function and those who did not. CONCLUSION: Volumetric assessment has no predictive value in differentiating between NPH patients who respond to ventriculoperitoneal shunt surgery and those who do not.